(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we Introduce new operators depending on the definitions of γ and γ^*-operators that were defined in amO. We provide some examples to illsturate the relation between these new operators. Additionally, we give more results regarding to γ-diamond operator.